Fractured Psyche and Corroded Self: The Sadomasochistic Dynamics in Jane Eyre - Ahmad, Syed Arslan; Saeed, Sohail Ahmad; Javed, Noveen (International Journal of Psychosocial Rehabilitation, 2020)
- The present analysis is a psychological study of Bronte’s Jane Eyre. Itidentifies the underlying causes to the emotional instability, lack of empathy, and proneness to psychological and physical harm, as found in the characters of Jane Eyre and Edward Rochester.The imbalanced pattern of behavior results from deeper, psychological issues in both characters. The study uses psychoanalysis as its core theory to argue that the recurrent deviance in behavior, and the alarming propensity to aggressive behavior in both characters is indicative of sadistic/masochistic formulation of personalities.The sadistic and masochistic impulses are the basis for the imbalanced state of mind and the perversion of pleasure in the characters.The characters direct their aggression inwards and/or outwards with unhealthy consequences as they either hurt others or their own selves in the process. The said pattern of behavior serves as an avenue for pleasure, and self-gratification. The study finds that pain, then, becomes a desired state of mind,and it relates thisdesire to cause harm with an over-active death instinct, whichresults in psychological, emotional and physical deterioration of both characters. The study further traces the roots of the destructive behavior to the early childhood experiences of both characters. Due to the disturbed childhood under the care of strict parental figures, Jane and Rochester develop an unhealthy propensity to violence. Specifically, the study argues that unresolved issues during the anal and Oedipal stages of development during childhoodbuild their destructive capacity of both characters, and result in the twisted sadistic/masochistic dynamics which are manifested later in life.